Exodus 2:1–10 and Dialectics on Maternal Virtues in Contemporary Igboland, Nigeria - Onyekachi Chukwuma (Old Testament Essays)
This study investigates the disposition of mothers in contemporary Igboland towards displaying traditional maternal virtues in the upbringing of their children. The inquiry is underpinned by a popular Old Testament narrative, Exodus 2:1-10. The pericope reports the story of the birth of Moses, who was born at the climax of a chaotic situation in Egypt. To control the numerical growth of the Israelites, the king of Egypt instructed that all Hebrew male babies be thrown into the Nile. When Moses was born, his mother, sister and Pharaoh’s daughter displayed age-long maternal qualities such as love, sacrifice, courage, wisdom and patience, to save him from Pharaoh’s plot. The study observes that in contemporary times, women have more opportunities for self-development and employment; they venture into diverse careers that could restrain them from exhibiting some longstanding motherly virtues in child upbringing. Feminist criticism, descriptive analysis and comparative analysis are employed in studying the text, the social phenomenon and the interaction between the text and the social context, respectively.